ANALISIS HUKUM ISLAM DAN HUKUM ‎POSITIF TERHADAP PEMBERIAN HIBAH ‎HARTA WARIS TERHADAP ANAK ANGKAT - Iqbal, Muhammad (Jurnal Ushuluddin, 2024)
Biological children and husband/wife are the only legitimate heirs of the parents' inheritance, and adopted children do not have such rights. This is because adopted children aren’t  included in the family tree of their adoptive parents. In addition, adopted children also believe that they have the right to receive it since they took care of their adoptive parents until they died, unlike their siblings who didn’t  play a role in the care. If there is a difference of opinion regarding who has the right to receive the inheritance, this can lead to disputes, especially between adopted children and other prospective heirs. This study namely library research. This type of research involves studying existing literature by searching for and analyzing books, journals, and other reference materials. Because they discuss the topic being studied both directly and indirectly. Islamic law and positive law, adopted children cannot legally separate themselves from their biological parents and must go through legal procedures to clarify and protect their position. If this has been done, the adopted child has the right to inherit one-third of the adoptive parents' assets, either through a gift or a mandatory willKeywords: Law, Grant, Adopted Child